Deception detection, transmission, and modality in age and sex - Sweeney, Charlotte D.; Ceci, Stephen J. (Frontiers in Psychology, 2014)
This study is the first to create and use spontaneous (i.e. unrehearsed) pro-social lies in an ecological setting. Creation of the stimuli involved fifty-one older adult and forty-four college student “senders” who lied “authentically” in that their lies were spontaneous in the service of protecting a research assistant. In the main study, seventy-seven older adult and eighty-four college raters attempted to detect lies in the older adult and college senders in three modalities: audio, visual, and audiovisual. Raters of both age groups were best at detecting lies in the audiovisual and worst in the visual modalities. Overall, college students were better detectors than older adults. There was an age-matching effect for college students but not for older adults. Older adult males were the hardest to detect. The older the adult was the worse the ability to detect deception.